Are body mass index and age independent risk factors for new-onset atrial fibrillation after cardiac surgery regardless of left atrial size and left ventricular ejection fraction value?. (25th November 2020) - Stefano, P; Bugetti, M; Michelucci, A; Del Monaco, G; Popescu, G; Pieragnoli, P; Ricciardi, G; Perrotta, L; Checchi, L; Rondine, R; Bevilacqua, S; Marchionni, N
Abstract: Background: Obesity, advanced age and left atrium dimensions have been linked to atrial fibrillation (AF). Purpose: This study aimed at evidencing if the above mentioned risk factors have a role among the others in conditioning the onset of post operative AF (PoAF) in patients undergoing cardiac surgery without previous AF. Methods: This study evaluated 249 consecutive patients undergoing coronary artery by-pass surgery either isolated or in combination with aortic or mitral valve repair/replacement, or isolated valve repair/replacement. Prior to surgery, in all patients the following data were collected: age (yrs), body mass index (BMI, kg/m 2 ), left atrium (LA) diameter (cm), LA area (cm 2 ), left ventricular ejection fraction (LVEF, %), the presence/absence of arterial hypertension (AH) and diabetes, creatinine (mg/dL). To detect the presence of PoAF, cardiac rhythm was continouosly recorded during the first seven postoperative days. Results: PoAF occurred in 127 patients (51%). We compared patients with and without PoAF. Mean values (±1 SD) of continuous variables and the frequency of dicothomic ones are reported in the table. No difference was observed for sex, LA diameter, LA area, LVEF and diabetes. Instead, patients with PoAF had higher values of age, BMI, creatinine and a greater prevalence of AH. According to multivariable binary logistic analysis the independent predictors of PoAF were: age (OR = 1.05, CI 95%: 1.026–1.074, p=0.018) and BMI (OR = 1.09, CI 95%: 1.015–1.171, p=0.0001). Conclusions: Results suggest that advanced age and a higher value of BMI could be strong risk factors for PoAF in patients who undergo cardiac surgery without previous AF. This considering that in the present population the values of LA diameter, LA area and LVEF showed no statistically significant difference between patients with and without PoAF. Funding Acknowledgement: Type of funding source: None